Towards an efficient in-network caching using federated learning - Djekidel, Malak Safa; Habib, Manal; Kerrache, Chaker (Laghouat : Université Amar Telidji - Département d'informatique, 2023)
In today’s digital age, the Internet has experienced a remarkable growth accompanied by an exponential increase in both the diversity of available content and the number of users. As a consequence, the demand for server resources and the volume of server requests have surged significantly. This places significant strain on servers, diminishing their ability to handle user demands effectively. To alleviate this issue, caching is employed to store frequently requested content in memory that is closer to users. However, determining which content should be cached poses a challenge. Efficient cache management plays a vital role in enhancing data access speed and overall efficiency. This challenge has been extensively studied and applied in the context of federated learning engineering, where effective cache management techniques are crucial for optimizing the performance of distributed machine learning models. By addressing cache management challenges, researchers aim to improve scalability, efficiency, and overall system performance, ultimately enhancing the effectiveness of federated learning methodologies. In our research, we conducted a study on the topic of enhancing network caching efficiency by implementing federated learning. Our study involved the creation of four users, each of whom assigned a portion of a movie database that included movie ratings. Our goal was to identify the most popular movies using artificiel neural network and cache them for each user, thus improving delivery services within the network by bringing these movies closer to the respective users.